A review on the current literature regarding the value of exosome miRNAs in various diseases - Senjie Li; Dongqing Lv; Hong Yang; Yan Lu; Yongping Jia (Annals of Medicine, 2023)
AbstractObjective: Exosome microRNAs (miRNAs) have great research outlook in clinical therapy and biomarkers, they have been found to have a close to multiple diseases. A growing number of studies have attempted to alleviate or treat diseases through exosomes. It indicates that miRNAs in exosomes have great significance in preventing and controlling diseases in clinical research. We summarise these studies below to better understand their implications.Methods: We screened and analyzed more than 100 articles from PubMed, Web of Science, and other databases from 1987 to 2022. Data of the clinical trials are collected from clinicaltrials.gov.Results: In this review, we introduce the source, type, and characteristics of several exosomes, summarising current research on their role in cardiovascular, nervous system disease, tumour, and other diseases. Further, we discuss their mechanism of action and future directions for development of treatments in several diseases, and highlight the significant research value and potential use of exosomes in clinical diagnosis and treatment.Conclusions: An increasing number of researchers have begun to explore the link between exosomal miRNAs and diseases. More exosome therapeutics will be used in future clinical trials, which may bring new hope for the diagnosis and treatment of several diseases.KEY MESSAGESExosomes have unique advantages in molecular transport and cell signal transduction.miRNAs play an essential role in the formation of multiple diseases.Research on the clinical application and potential value of exosomes is growing.